Feasibility study of coconut coir dust briquette - Saha, KK; Hossain, MM; Ali, MR; Alam, MM (Journal of the Bangladesh Agricultural University, 2016)
This research work was conducted on economic feasibility of briquette made of coconut coir dust mixed with rice husk at different ratio. This study sought to assess the physical properties and calorific value of briquette and to establish the demand and willingness of potential users to substitute rice husk briquette and firewood. It was observed that briquette made from mixed coconut coir dust and rice husk at the ratio of 1:2 and 1:1 had desirable properties as compared to rice husk briquette. The percent of shatter indices, density, percent of resistance to water penetration, degree of densification and calorific value of briquette of mixing ratio 1:2 were found 99.75, 1.52gm/cc, 87.5, 11.35 and 4043 kcal/kg and of mixing ratio 1:1 were found 99.82, 1.48gm/cc, 87.5, 10.84 and 3657 kcal/kg, respectively. In case of rice husk briquette, the above values were 99.21, 1.40gm/cc, 75, 10.66 and 3537 kcal/kg, respectively. The production costs of mixing ratio 1:2 and 1: 1 were 3.27 Tk/kg and 3.10 Tk/kg, respectively which were lower than that of rice husk briquette. In partial budget, the substitution propositions among the selected briquettes indicated that coconut coir dust briquette of mixing ratio 1:1 appeared as the most impressive one. J. Bangladesh Agril. Univ. 12(2): 369-376, December 2014